Nutrimi di Storie Prendersi cura attraverso medium culturali - Milena Mazzara, Elena Gigante, Domenico Ferrara (Phenomena Journal, 2020)
When we talk about personality we refer to the psychical characteristics on which the personal identity of an individual is built, characteristics which distinguishes a person from others and determines its behavior and personal relationships. The individual personality develops throughout the course of our lives, modeling when we are small and consolidating with the psychological and cognitive maturation of the adult, influenced and punctuated by the development of different aspects of our ego. The attachment theory elaborated by John Bowlby, claims that in small human beings there is an innate tendency to search for one adult figure, able to provide care and protection, in times of need and danger. This guarantees the newborn to satisfy his/her physiological needs which permit to survive, that otherwise immaturity and ontogenetic inability would not allow. Depending on the characteristics of the interaction between the child and the caregiver, they will be configured in the first, some attachment styles/patterns, that is, strategies of thought and behavior that the child develops to increase the probability of receiving care and protection from his attachment figure. With this work we hope to verify if the symbolic world of the story, as a translated experience of the processes related to attachment, allows the mother and the child to say in metaphor what is potentially threatening in the relationship of ongoing attachment. Active and interactive reflection of the adult and the child together, can facilitate knowledge, consciousness and therefore change. Through the symbolic world of the story, mother and child tell each other in a metaphor what is reasonable and acceptable to hear and express and what is instead, potentially threatening the state of their relation. Once clinical validity of the instrument is verified, we expect to build an integrated method for the secondary prevention of attachment style which would be in progress.